Feasibility assessment of an Organic Rankine Cycle (ORC) cogeneration plant (CHP/CCHP) fueled by biomass for a district network in mainland Spain. (15th August 2017) - Uris, María; Linares, José Ignacio; Arenas, Eva
Abstract: A previously developed procedure to evaluate a biomass plant feasibility has been improved, now considering availability and cost of the biomass resources around the plant's location. The plant is an organic Rankine cycle cogeneration facility located in mainland Spain. All the villages over 15.000 inhabitants have been considered as potential locations. Partial load operation is considered as well as cogeneration (CHP) and trigeneration (CCHP) schemes. Biomass calculations were performed using BIORAISE (a free GIS tool) showing that, in all the locations, the available biomass within a 30-km radius is larger than the demand, with an average cost of 10 €/MWh. No subsidies have been considered. In CHP operation, all the locations lead to "high efficiency cogeneration" plants, with the best profitability in medium-severe to severe-winter climate zones. In CCHP mode, only locations in medium-to severe-winter climate zones reach "high efficiency". This mode is worthwhile in climate zones with mild winters and medium to hot summers. The optimum plant size is found to be smaller in CCHP compared to CHP in all the locations and the biggest plants are situated in climate zones with severe winters. Avoided CO2 emissions reach higher values in CHP mode compared to CCHP. Highlights: Feasibility assessment of a biomass cogeneration plant has been carried out. Biomass availability and cost have been estimated using GIS tool BIORAISE. Climatic zones in mainland Spain have been characterized by profitability. CCHP configuration is worth in regions having mild winters and medium-to hot summers. According to PES, CHP configuration leads in all regions to "high efficiency cogeneration".